PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN KREATIF BAGI GURU MI DI KOTA LHOKSEUMAWE - Sarah Fazilla,; Noval Fuadi,; Abdul Kadir,; Anisaturrahmi,; Fauziana,; Sari, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Learning activities at the basic education level, especially Madrasah Ibtidaiyah are expected to develop children's abilities and creativity well, this can be realized by preparing appropriate materials, methods and media in teaching and learning activities. In the learning process at Madrasah Ibtidaiyah, namely MIN 3 and MIN 4 in Lhokseumawe City, it was found that currently teachers have used learning media, but the media is only in simple form and has not been used in all teaching materials. From the existing problems, it is necessary to design an activity that can support the development of teacher skills at Madrasah Ibtidaiyah in order to better understand the concept of learning media accurately and be able to apply it directly in the learning process at Madrasah Ibtidaiyah. The method that will be implemented in this activity is the direct practicum method and the lecture method. Based on the results of the training and mentoring activities in this service activity, it can be concluded: 1) This training activity is able to inspire and motivate teachers in selecting and designing appropriate learning media and in accordance with the expected learning objectives; 2) The training that has been held is able to improve teacher competence and special skills in improving the quality of learning in each madrasah Ibtidaiyah.